Investigating In Vitro Antibacterial Activities of Medicinal Plants Having Folkloric Repute in Ethiopian Traditional Medicine - Mekonnen Sisay MSc; Negussie Bussa PhD; Tigist Gashaw MSc; Getnet Mengistu MSc (SAGE Publishing, 2019)
Medicinal plants are targeted in the search for new antimicrobial agents. Nowadays, there is an alarmingly increasing antimicrobial resistance to available agents with a very slow development of new antimicrobials. It is, therefore, necessary to extensively search for new agents based on the traditional use of herbal medicines as potential source. The antibacterial activity of 80% methanol extracts of the leaves of Verbena officinalis (Vo-80ME), Myrtus communis (Mc-80ME), and Melilotus elegans (Me-80ME) was tested against 6 bacterial isolates using agar well diffusion technique. In each extract, 3 concentrations of 10, 20, and 40 mg/well were tested for each bacterium. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were also determined. Vo-80ME and Mc-80ME exhibited promising antibacterial activity against Staphylococcus aureus with the highest zone of inhibition being 18.67 and 26.16 mm, respectively at concentration of 40 mg/well. Regarding gram-negative bacteria, Vo-80ME exhibited an appreciable activity against Escherichia coli and Salmonella typhi . Mc-80ME displayed remarkable activity against all isolates including Pseudomonas aeruginosa with the maximum zone of inhibition being 22.83 mm. Me-80ME exhibited better antibacterial activity against E coli, but its secondary metabolites had little or no activity against other gram-negative isolates. The MIC values of Vo-80ME ranged from 0.16 to 4.00 mg/mL. The lowest MIC was observed in Mc-80ME, with the value being 0.032 mg/mL. Mc-80ME had bactericidal activity against all tested bacterial isolates. Mc-80ME showed remarkable zone of inhibitions in all tested bacterial isolates. Besides, Vo-80ME showed good antibacterial activity against S aureus , E coli , and S typhi. Conversely, Me-80ME has shown good activity against E coli only. Generally, M communis L and V officinalis have good MIC and MBC results.